Garden Birds: How to Attract Birds to Your Garden - Proctor, Noble S.; Walker, Cyril Alexander; Parmenter, Tim (Rodale Press, 1986)
Includes a directory of 100 birds, describing their migration, habitat, scientific name, and physical characteristics.
Keywords: Bird attracting; Garden animals; dept.bio; faculty_collection